Examining the quality of phonological representations in Anindilyakwa children in Australia. Issue 6 (19th July 2015) - Fletcher, Janet; Hogben, John; Neilson, Roslyn; Lalara, Rhoda Dugurruru; Reid, Corinne
Abstract Background In attempting to evaluate an intervention programme designed to improve English literacy outcomes in children in a remote indigenous community in Australia, the need for valid and culturally appropriate measures of the factors likely to impact on literacy development became apparent. One factor considered likely to be of importance was the precision of the children's phonological representations. Aims To develop a measure of phonological representations that was culturally relevant for Anindilyakwa children and to evaluate its reliability and concurrent validity against English measures that are known to be predictive of literacy outcomes. Methods & Procedures Starting from the Quality of Phonological Representations test (QPR), the authors developed an Anindilyakwa Quality of Phonological Representations test (AQPR) and examined its reliability and concurrent validity. Outcomes & Results The AQPR was found to have acceptable reliability and to correlate significantly with three well‐established measures of phonological awareness and phonics in English. Conclusions The AQPR would thus seem an appropriate screening test for use by teachers to identify Anindilyakwa children in need of interventions to improve phonological representations before exposing them to an English literacy programme for which they may not yet be ready. The process involved in its development could be used by others working with indigenous students.